Biofilms can act as plasmid reserves in the absence of plasmid specific selection - Henriette Lyng Røder (Nature Portfolio, 2021)
Abstract Plasmids facilitate rapid bacterial adaptation by shuttling a wide variety of beneficial traits across microbial communities. However, under non-selective conditions, maintaining a plasmid can be costly to the host cell. Nonetheless, plasmids are ubiquitous in nature where bacteria adopt their dominant mode of life - biofilms. Here, we demonstrate that biofilms can act as spatiotemporal reserves for plasmids, allowing them to persist even under non-selective conditions. However, under these conditions, spatial stratification of plasmid-carrying cells may promote the dispersal of cells without plasmids, and biofilms may thus act as plasmid sinks.